Phase I Trial of a Third Generation EGFR Mutant-Selective Inhibitor (D-0316) in Patients with Advanced Non-Small Cell Lung Cancer. (26th February 2022) - Jian, Hong; Wang, Kai; Cheng, Ying; Ding, Lieming; Wang, Yang; Shi, Zhe; Zhang, Ling; Wang, Yaolin; Lu, Shun
Abstract: Background: D-0316 is a third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) developed for patients with locally advanced or metastatic non-small cell lung cancer (NSCLC) with EGFR T790M mutation that progressed after prior treatment with the first- or second-generation EGFR-TKI. Methods: This phase I, open-label, multicenter clinical trial evaluated daily oral D-0316 administration in dose-escalation (25 to 150 mg; 17 patients) and dose-expansion (50, 100 mg; 67 patients) cohorts for safety, tolerability, anti-tumor activity, and pharmacokinetics. Results: D-0316 was well tolerated at daily doses of 25 to 150 mg and the maximum tolerated dose (MTD) was not reached. The most common treatment-related adverse events (AEs) were platelet count decreased, electrocardiogram QT corrected interval prolonged, anemia, rash, low white blood cell count, hypertriglyceridemia, high cholesterol, headache, pruritus, cough, and aspartate transaminase (AST) or alanine transaminase (ALT) increased. Most of AEs were grade 1 or 2. In the 50 and 100 mg group, the overall response rate (ORR) was 33.3% and 45.5%, the disease control rate (DCR) was 86.7% and 93.9%, and the median PFS was 8.3 and 9.6 months, respectively. D-0316 exposure increased in proportion to dose from 25 to 150 mg. The recommended phase II dose (RP2D) was 100 mg. Conclusion: D-0316 is safe, tolerable, and effective for patients with locally advanced/metastatic NSCLC with the EGFR T790M mutation who previously received EGFR-TKI. ClinicalTrials.gov Identifier: NCT03452150. Abstract : The first- and second-generation EGFR tyrosine kinase inhibitors are now used worldwide to treat advanced non-small cell lung cancer (NSCLC); however, patients taking these drugs develop different degrees of acquired drug resistance and need to switch to new treatments. The present study was a first-in-human phase I study to evaluate the safety, efficacy, and pharmacokinetics of D-0316 in patients with advanced NSCLC.